Inhibitory effects of sophocarpine on animal tumors - LI Xue-mei; LI Lan-zhen; CHEN Shao-li; QIU Xiang-huan; YU Yue-hua; PAN Da-xin; ZOU Li-ling; YANG Zi-lan; HAN Yu-sheng (Acta Pharmacologica Sinica, 2016)
Sophocarpine an alkaloid isolated from Sophora alopecuroides L., is a new type of drug for choriocarcinoma. In mice rats and 615 inbred mice, the transplanted tumors of S180, U14, Lio 1, W256, and L 615 were inhibited moderately by sophocarpine. The rates of inhibition were 31-56% based on the tumor weights. No side effect was noted. When sophpcarpine was given ip to miceinoculated with S180 ascites sarcoma or Ehrlich ascites carcinoma or W256, the mitotic indices of cancer cells were moderately or slightly reduced. The mitochondria of S180 sarcoma cells showed swelling and dissolution vacuolations were found inside the cytoplasm of tumor cells. The microvilli of the cell membrane were diminished. When normal mice or S 180. U 14 solid tumor-bearing mice were given ig sophocarpine 60 mg/kg qd×10 d, the contents of RNA and DNA in tumor or spleen decreased slightly. In dogs iv sophocarpine 30 mg/kg qd×23 d, no toxicity was seen. When the dose was incteased to 45 mg/kg. mild reversible thrombopenia was observed. Studies on the phagocytic reaction of macrophage and concomitant tumor immunity during sophocarpine treatment on mice showed no marked influence on immune activity.